THE ROLE OF GAS6 IN LEFT VENTRICLE REMODELLING IN PATIENTS WITH CHRONIC HEART FAILURE OF ISCHEMIC ORIGIN AND CONCOMITANT TYPE 2 DIABETES MELLITUS AND OBESITY - Borovyk, Kateryna; Kadykova, Olga; Kravchun, Pavlo (Eastern Ukrainian Medical Journal, 2025)
Introduction. Chronic heart failure (CHF) remains a global pandemic, and the prognosis is particularly poor for patients with ischaemic CHF against a background of concomitant type 2 diabetes mellitus (T2DM) and obesity. A key process determining the progression of CHF is pathological remodelling of the left ventricle (LV). The protein GAS6 (Growth Arrest-Specific 6), a ligand of the TAM family of receptors, is involved in the regulation of inflammation, fibrosis and proliferation. The specific role of the GAS6/TAM system in the complex process of LV remodelling in this high-risk cohort of patients remains poorly understood. The relevance of the work is consistent with UN Sustainable Development Goal No. 3.The aim is to study the role of GAS6 protein as a potential biomarker and pathophysiological mediator of left ventricle remodelling in patients with chronic heart failure at the background of coronary artery disease with concomitant type 2 diabetes mellitus and obesity.Materials and methods. The study included 75 patients with CHF against the background of coronary artery disease (CAD), T2DM and obesity. The inclusion criteria were age over 18 years, presence of CAD with signs of CHF, T2DM, presence of overweight/obesity of 1-3 degrees or their absence, and written consent. Exclusion criteria included acute and oncological diseases, chronic renal failure with GFR < 35 ml/min/1.73 m², and acute coronary/cerebral events within 6 months. Patients were divided into 2 subgroups: subgroup 1 – GAS6 < 31.64 ng/ml (n=36), subgroup 2 – GAS6 > 31.64 ng/ml (n=39). Echocardiography was performed, including assessment of ventricular-arterial coupling (VAC) as the ratio of effective arterial elasticity to end-systolic elasticity of the LV (Ea/Es). GAS6 levels were determined by enzyme-linked immunosorbent assay (ELISA).Results and Discussion. The study demonstrated that structural and functional changes in the myocardium were most unfavourable in patients with higher GAS6 levels (subgroup 2). The following statistically significant differences (p<0.05) were found in the 2nd subgroup compared to the 1st: end-systolic volume was 42.47% higher, and end-diastolic volume was 28.84% higher; LV ejection fraction was significantly lower by 25.52%; LV myocardial mass and LV myocardial mass index were higher by 25.71% and 12.23%, respectively; the Ea/Es ratio was significantly higher by 35.09%, indicating severe cardiovascular dysfunction. Correlation analysis confirmed direct, statistically significant associations between GAS6 levels and most remodelling parameters, including a strong direct association with end-systolic dimension (r=0.71).Conclusions. GAS6 protein levels > 31.64 ng/ml are associated with a more pronounced dilated type of left ventricular remodelling, significantly reduced pumping function, and significant ventricular-arterial coupling impairment, emphasising its role as a potential marker of unfavourable chronic heart failure progression in conditions of polymorbidity.